Planning, Design and Construction of Gabion Structure for Soil and Water Conservation in Malwa Region - Kool, Y.M.; Gupta, R.K.; Shrivastava, N.C.; Shroff, V.N. (Journal of Soil and Water Conservation, 2022)
The gabion is a stop darn-cum-drop structure constructed by using double galvanized wire mesh as a reinforcement material to bind loose boulders, which prevents soil erosion and regulate the flow of water. Planning, design and construction features of gabion are presented for 30 ha small watershed area. The crest length is 6 in for expected discharge of 4.5 cumec. The ratio of submerged area with watershed area has been worked out 1:94, while cost of construction as Rs. 725/m3. The volume of water storage is 2340 m3 at a cost of Rs. 6.75/1000 lit which also protect 975 m of productive soil from flowing out of the area. Gabion structures are found suitable for retaining productive top soil, which otherwise is carried away by the flowing water and also help in conservation of moisture for agricultural use.